2019
DOI: 10.1038/s41598-019-54566-4
|View full text |Cite
|
Sign up to set email alerts
|

Bone secreted factors induce cellular quiescence in prostate cancer cells

Abstract: Disseminated tumor cells (DTCs) undergo a dormant state in the distant metastatic site(s) before becoming overt metastatic diseases. In prostate cancer (PCa), bone metastasis can occur years after prostatectomy, suggesting that bone may provide dormancy-inducing factors. To search for these factors, we prepared conditioned media (CM) from calvariae. Using live-cell imaging, we found that Calvarial-CM treatment increased cellular quiescence in C4-2B4 PCa cells. Mass spectrometry analysis of Calvarial-CM identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 80 publications
(136 reference statements)
1
28
0
Order By: Relevance
“…In a murine model of melanoma metastasis, it was found that for malignant tumors with RANK expression, RANKL produced by osteoblasts and bone marrow stromal cells could act as a chemical attractant and promote the migration and metastasis of malignant tumors to these sites ( 132 ). Similar effects were also found in malignant tumors such as breast cancer ( 97 , 133 135 ), prostate cancer ( 136 138 ), and lung cancer ( 100 , 104 , 139 ). The activation of phospholipase C (PLC), protein kinase C (PKC), ERK, and phosphatidylinositol-3-OH kinase (PI(3)K) pathways were involved in RANK-induced tumor cell migration ( 140 143 ).…”
Section: Rank/rankl As Regulators Of Metastasissupporting
confidence: 66%
“…In a murine model of melanoma metastasis, it was found that for malignant tumors with RANK expression, RANKL produced by osteoblasts and bone marrow stromal cells could act as a chemical attractant and promote the migration and metastasis of malignant tumors to these sites ( 132 ). Similar effects were also found in malignant tumors such as breast cancer ( 97 , 133 135 ), prostate cancer ( 136 138 ), and lung cancer ( 100 , 104 , 139 ). The activation of phospholipase C (PLC), protein kinase C (PKC), ERK, and phosphatidylinositol-3-OH kinase (PI(3)K) pathways were involved in RANK-induced tumor cell migration ( 140 143 ).…”
Section: Rank/rankl As Regulators Of Metastasissupporting
confidence: 66%
“…High BMP1 levels predict poor survival in cancers such as renal clear-cell carcinoma (ccRCC) 35 but predict better survival in breast cancer 36 . BMP1 enhances malignancy of hepatocellular carcinoma 37 and ccRCC 35 , promotes cancer cell motility in gastric cancer 38 , but induces cellular quiescence in prostate cancer cells 39 . Here, we showed that BMP1 can suppress tumor growth and metastasis in PDAC models by promoting fibrillar collagen deposition, but only in cancer cells expressing substantial amounts of collagen.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent study has shown that induction of DKK3 can inhibit prostate cancer development [ 8 ]. DKK3 could induce cellular quiescence in prostate cancer cells through activating the p38MAPK signaling pathway [ 9 ]. Further, it was noted that DKK3 mediated Wnt/β-catenin pathway and thereby suppressed in cellular processes in prostate cancer and hepatocellular carcinoma, incorporating with miRNA [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%